UPAYA PENINGKATAN KINERJA PERANGKAT DESA CANGGAL KECAMATAN CANDIROTO KABUPATEN TEMANGGUNG - Dina Listiyana; Meidi Syaflan (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study aims to improve the performance of Canggal Village apparatus, Candiroto District, Temanggung Regency. The research was carried out starting in October 2022. This type of research is descriptive qualitative. Collection of interview and observation data. Interactive Model Miles and Huberman. The results showed that: 1) The performance of the Canggal Village apparatus, Candiroto District, Temanggung Regency was not on target because: most of the village officials were elderly, the motivation of village officials was in the low category, the skills, knowledge and development of village officials were still low, the facilities and infrastructure were inadequate. 2) Efforts to improve the performance of Canggal Village officials, Candiroto District, Temanggung Regency, namely: not giving a heavy workload to elderly village officials and completing workloads for younger staff so that work can be completed on target, providing motivation to village officials by providing rewards for village officials who excel, include education, training and development for village officials, especially for the use of information technology and improve facilities, facilities and infrastructure such as procuring laptops and increasing internet network bandwidth, as well as imposing sanctions on village officials who are not disciplined.